Perceptions of precision medicine among diverse dementia caregivers and professional providers - Joseph E. Gaugler; Hayley R. McCarron; Lauren L. Mitchell (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Underrepresented groups experience health disparities and a history of exploitation by researchers and the health‐care system that may contribute to distrust of new treatments and technologies. This study aims to understand how diverse family caregivers and health‐care professionals view the benefits and risks of precision medicine as well as cultural dimensions to consider when developing and implementing precision medicine interventions in dementia care. Methods Eight focus group sessions and one individual interview were conducted over a 6‐month period. Fifty‐four focus group participants included African‐American, American Indian, rural Caucasian, Latino, and West African caregivers and health professionals. The majority of participants were female (73%) and were of Hispanic/Latino ethnicity (68%). About a third of participants identified their race as white. Participants were presented with four hypothetical scenarios related to precision medicine diagnostic and treatment approaches in dementia care: (1) genetic testing for dementia risk, (2) health‐care informatics to determine individualized medication dosages based on health and family history, (3) a smartphone application providing dementia caregiving tips, and (4) remote activity monitoring technology in the home. Focus groups' responses were coded using thematic analysis. Results Participants indicated skepticism regarding the use of precision medicine in their communities. Concerns included cost of precision medicine and insurance coverage; lack of alignment with cultural norms; fraught relationships between communities, health professionals, and researchers; data ownership and privacy; and the trade‐off between knowing risk and treatment benefit. Discussion Establishing relationships with underserved communities is crucial to advancing precision medicine in dementia care. Appropriate engagement with diverse racial, ethnic, and geographic communities may require significant investment but is necessary to deliver precision medicine effectively.